The cost of the diagnostic odyssey of patients with suspected rare diseases - Rick Glaubitz; Luise Heinrich; Falko Tesch; Martin Seifert; Katrin Christiane Reber; Ursula Marschall; Jochen Schmitt; Gabriele Müller (Orphanet Journal of Rare Diseases)
Abstract Purpose Patients with rare diseases often undergo a long diagnostic odyssey. However, there is little empirical evidence on the cost incurred during the diagnostic pathway for patients with suspected rare diseases. This study provides a comprehensive analysis of healthcare costs and utilization during the diagnostic pathway for a heterogeneous sample of patients with suspected rare diseases but unclear diagnosis. Methods Using claims data from five German statutory health insurance organizations for the years 2014–2019, we analyzed costs and healthcare utilization of 1,243 patients (aged 0 to 82 years) with suspected rare diseases referred to a rare disease center. A control cohort was assigned using 1:75 exact matching on age, sex and place of residence. Results In the years prior to referral to an expert center, healthcare utilization of patients with suspected rare diseases was, on average, substantially and significantly higher compared to a matched control cohort during the same observation period – e.g. in terms of the number of hospitalizations (3.1 (95%CI: 2.9–3.4) vs. 0.5 (95%CI: 0.5–0.5)), different diagnoses (50.0 (95%CI: 48.1–51.9) vs. 26.4 (95%CI: 26.2–26.5)), different active substances prescribed (12.7 (95%CI: 12.2–13.3) vs. 8.2 (95%CI: 8.2–8.3)) and the number of genetic tests (14.7 (95%CI: 12.6–16.7) vs. 0.3 (95%CI: 0.3–0.3)). We found evidence of heterogeneity in utilization by age and sex. On average, direct costs (inpatient, outpatient and prescription drug costs) of patients with suspected rare diseases during the diagnostic pathway were 7.6-fold higher than the costs of matched controls (€26,999 (95%CI: €23,751 − 30,247) vs. €3,561 (95% CI: € 3,455-3,667)). Inpatient costs were the main cost component, accounting for 62.5% of total costs. Conclusions The diagnostic odyssey of patients with suspected rare diseases is associated with extensive healthcare utilization and high cost. Against this background, new ways to shorten the diagnostic journey have a high potential to decrease the financial burden related to rare diseases.